Judo: The roads to ippon: biomechanics of throws tactics in competition with suggestions aimed at enhancing effectiveness of coaches tools - Sacripanti, A. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
In this invited lecture the biomechanical analysis of tactical tools utilized by top athletes in high level competition is presented. In the first part, the lecture starts with a very short summary of the researches carried out on biomechanics, thermal exchange and metabolic energy expenditure related to judo throwing techniques. These data elicit the division in more and less energetically expensive and in most and least efficient techniques in term of mechanical power applied. Both these divisions are strictly connected to the biomechanical classification of throws in Lever and Couple.